Therapeutic engagement in robot‐assisted psychological interventions: A systematic review. (23rd December 2021) - Riches, Simon; Azevedo, Lisa; Vora, Alkesh; Kaleva, Ina; Taylor, Lawson; Guan, Peipei; Jeyarajaguru, Priyanga; McIntosh, Harley; Petrou, Constantina; Pisani, Sara; Hammond, Neil
Abstract: Purpose: Therapeutic engagement is a key component of psychological interventions. Robot‐assisted psychological interventions appear to have therapeutic benefits for service users that are challenging to engage. However, engagement with robots in robot‐assisted psychological interventions is not well understood. The aim of this systematic review is to evaluate the quality of therapeutic engagement in robot‐assisted psychological interventions (PROSPERO: 122437). Methods: Scopus, Web of Science, PsycInfo and Medline were searched until 15 January 2021 for studies which quantitatively evaluated therapeutic engagement in robot‐assisted psychological interventions. The Effective Public Health Practice Project (EPHPP) quality assessment tool was used to assess methodological dimensions of studies. Results: 3647 studies were identified through database searching. Thirty studies ( N = 1462), published between 2004 and 2020, and from 14 countries, were included. Robots were typically toy animals or humanoids and were used to provide support and improve wellbeing through social interaction. Studies primarily tested robots on older adults with dementia and children with autism and indicated positive therapeutic engagement. Twelve studies included a control group. EPHPP ratings were 'strong' ( N = 1), 'moderate' ( N = 10) and 'weak' ( N = 19). Conclusions: Therapeutic engagement between service users and robots is generally positive. Methodological limitations of studies, such as small sample sizes, and lack of control groups and longitudinal data, mean that the field is in early stages of its development and conclusions should be drawn with caution. There are important practical and ethical implications for policymakers to consider, such as responsible clinical practice and how service users may understand the therapeutic relationship with robots.